1999
DOI: 10.1177/002215549904700109
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Acetylcholine Transporter in the Rat Cochlear Nucleus: An Immunohistochemical Study

Abstract: SUMMARY After being synthesized in the cytoplasm of axon terminals, acetylcholine is packaged into synaptic vesicles by a proton-dependent transporter, vesicular acetylcholine transporter (VAChT). Localization of VAChT is restricted to cholinergic neurons, especially their terminals. We used an anti-VAChT antibody from INCSTAR to localize cholinergic terminals in the rat cochlear nucleus (CN), an important brainstem auditory center. VAChT immunoreactivity in the rat CN appears as labeled puncta and a few conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…This finding is in line with earlier reports showing the presence of the nicotinic acetylcholine receptors in the rat CN without apparent function [13,43]. The results presented here also underscore a dominant role of the muscarinic receptors in the cholinergic modulation of the granule neurones.…”
Section: Muscarinic Modulation Of Dcn Granule Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with earlier reports showing the presence of the nicotinic acetylcholine receptors in the rat CN without apparent function [13,43]. The results presented here also underscore a dominant role of the muscarinic receptors in the cholinergic modulation of the granule neurones.…”
Section: Muscarinic Modulation Of Dcn Granule Cellssupporting
confidence: 93%
“…For example, it has been shown that cholinergic axons originating from the trapezoid nucleus [33] and from the superior olivary complex [11] terminate in the CN, and vesicular choline acetyltransferase positive boutons have been described to contact various cell types of the CN [43]. Moreover, expression of muscarinic receptors has been demonstrated, along with their expression patterns, in the CN [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…VAChT labeling in axons and axon terminals was affiliated primarily with small synaptic vesicles. These findings are in agreement with previous electron microscopic studies in other brain regions (Yao and Godfrey, 1999;Garzón and Pickel, 2000;Turrini et al, 2001) and are consistent with the role of VAChT in packaging acetylcholine into synaptic vesicles (Usdin et al, 1995). Within VAChT-labeled terminals and axons, ER␣-IR also was localized to clusters of small synaptic vesicles, suggesting localized modulation of the same portions of terminal membranes.…”
Section: Vacht-ir Presynaptic Profiles Contained Er␣ Immunoreactivitysupporting
confidence: 92%
“…The finding that their location overlapped with the cholinesterase-positive area (Osen and Roth 1969;Osen et al 1984;Yao and Godfrey 1995) indicates that Golgi cells can receive cholinergic innervation. VAChT is a marker for cholinergic terminals (Arvidsson et al 1997;Gilmor et al 1996;Yao and Godfrey 1999b). Double immunolabeling with antibodies for GFP and VAChT showed VAChT-immunopositive puncta closely apposed to the GFP-positive somata (Fig.…”
Section: Immunohistochemical Characterization Of Gfp-positive Cells Amentioning
confidence: 88%